The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1128/mcb.00951-12
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of Hypoxia-Inducible Factor 1α Ameliorates Adipose Tissue Dysfunction

Abstract: Hypoxia-inducible factor 1␣ (HIF1␣) induction in adipocytes is a critical component of the "fibrotic response," directly linked to metabolic dysfunction in adipose tissues under hypoxic conditions. We reasoned that inhibition of HIF1␣ may ameliorate the negative aspects of the obesity-associated fat pad expansion. We used the selective HIF1␣ inhibitor PX-478, whose effectiveness has previously been established in tumor models. We demonstrate that PX-478 treatment effectively suppresses the high-fat-diet (HFD)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
175
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(195 citation statements)
references
References 62 publications
6
175
1
Order By: Relevance
“…PX-478 has been shown to decrease Hif1α both in vitro and in vivo by decreasing Hif1α mRNA levels and blocking Hif1α mRNA translation (27,30,31). Constitutive VEGF signaling abrogates the effect of PX-478 on downstream angiogenic signaling, confirming that its effect is upstream of VEGF.…”
Section: Discussionsupporting
confidence: 53%
“…PX-478 has been shown to decrease Hif1α both in vitro and in vivo by decreasing Hif1α mRNA levels and blocking Hif1α mRNA translation (27,30,31). Constitutive VEGF signaling abrogates the effect of PX-478 on downstream angiogenic signaling, confirming that its effect is upstream of VEGF.…”
Section: Discussionsupporting
confidence: 53%
“…Consistently, several studies point to the role of macrophages in promoting fibroblastic phenotype and ECM production in human preadipocytes [33][34][35] . Taken together with recent observations that activation of hypoxia-inducible factor-1 in adipocytes contributes to interstitial fibrosis in adipose tissue 8 , Mincle in macrophages may link obesity-induced adipocyte damages with myofibroblast formation.…”
Section: Discussionmentioning
confidence: 88%
“…In this regard, Khan et al 6 reported that mice lacking collagen VI, which is expressed abundantly in adipose tissue, exhibit the uninhibited adipose tissue expansion and substantial improvement in insulin sensitivity on a high-fat diet (HFD). Although recent evidence suggests a role for obesity-induced hypoxic state 7,8 , the molecular mechanisms underlying adipose tissue fibrosis are still largely unknown.…”
mentioning
confidence: 99%
“…Inhibition of Hif-1a by disruption of its gene in adipocytes (30) or administration of its inhibitor (31) or antisense oligonucleotides (32) attenuates the consequences of an HFD in mice. Currently, no explanation is available for the discrepancy between those data and the beneficial effects of Hif-a stabilization by Hif-p4h-2 deficiency, but the additional stabilization of Hif-2a has been suggested to possibly play an important role (25).…”
Section: Discussionmentioning
confidence: 99%